Cowboys - Matthews, Leonard, 1920-; Rourke, Arlene C., 1944- (Vero Beach, Fla. : Rourke Publications, 1988)
Describes the development of cattle ranches and the day-to-day life and work of the cowboy.
Sch Libr Jnl
Keywords: Cowboys -- Juvenile literature. -- West (U.S.); Frontier and pioneer life -- Juvenile literature. -- West (U.S.); Cowboys; Ranch life; West (U.S.) -- Social life and customs; West (U.S.) -- Social life and customs; West (U.S.) -- Social life and customs